Brain endothelial- and epithelial-specific interferon receptor chain 1 drives virus-induced sickness behavior and cognitive impairment - Blank, Thomas; Detje, Claudia Nadine; Spieß, Alena; Wolfart, Jakob; Papageorgiou, Ismini E.; Schneider, Justus; Kann, Oliver (Immunity, 2016)
Sickness behavior and cognitive dysfunction occur frequently by unknown mechanisms in virus-infected individuals with malignancies treated with type I interferons (IFNs) and in patients with autoimmune disorders. We found that during sickness behavior, single-stranded RNA viruses, double-stranded RNA ligands, and IFNs shared pathways involving engagement of melanoma differentiation-associated protein 5 (MDA5), retinoic acid-inducible gene 1 (RIG-I), and mitochondrial antiviral signaling protein (MAVS), and subsequently induced IFN responses specifically in brain endothelia and epithelia of mice. Behavioral alterations were specifically dependent on brain endothelial and epithelial IFN receptor chain 1 (IFNAR). Using gene profiling, we identified that the endothelia-derived chemokine ligand CXCL10 mediated behavioral changes through impairment of synaptic plasticity. These results identified brain endothelial and epithelial cells as natural gatekeepers for virus-induced sickness behavior, demonstrated tissue specific IFNAR engagement, and established the CXCL10-CXCR3 axis as target for the treatment of behavioral changes during virus infection and type I IFN therapy.
Gesehen am 13.05.2020